Make and Test Projects in Engineering Design Creativity, Engagement and Learning - Samuel, Andrew Emery; SpringerLink (Online service) (London : Springer London, 2006)
This is a book about the invention and testing of ideas. By describing how to generate engaging problem situations for engineering students to solve it inspires original currents of thought. Make-and-test (MaT) is a practical way of testing ideas that challenges the validity of the ideas themselves and the manufacturing skills of the participants. Much of the project work described makes use of such simple materials as balsa wood and candle wax with the occasional appearance of the more exotic: fibre-glass-epoxy composites, for example; the properties and uses of these are examined in depth. All of the inventions described are intended to be well within the range of ingenuity and skills of first- and second-year engineering undergraduates. They can also be useful in stimulating the problem-solving skills of professional engineering and architectural designers so that everyday design questions and more one-off and personal undertakings such as the periodic design challenges offered by professional engineering societies can be interpreted more creatively. The major part of the book is devoted to case examples based on the author$1 (Bs twenty-five years of experience in supervising MaT work but there are many opportunities and exercises throughout the text to explore new MaT projects. In essence, Make and Test Projects in Engineering Design encapsulates the experience of engineering design from the uncertainty of "Can I tackle this problem?" to the joyous "Aha!" when a solution is discovered. An invaluable teaching tool and resource for the engineering educator and all those planning and conducting make and test projects, this is the first book that formalises an important aspect of early learning in engineering design.s
Invention, Creativity, Engagement: MaT Projects -- The Genesis and Development of MaT Projects -- Properties and Application of Some Unconventional Engineering Materials -- MaT Projects for Static Load-bearing Structures -- Dynamic MaT Projects: Things That Go (3z(BBump(3y (B-- Case Examples of Dynamic MaT Projects -- Concluding Notes and Some (3z(BCUTIEs(3y(B.s
Keywords: Engineering; Industrial design; Mechanical engineering; Engineering design; Materials science; Engineering; Engineering Design; Engineering, general; Learning & Instruction; Industrial Design; Characterization and Evaluation of Materials; Mechanical Engineering; Electronic books